RECENT ADVANCES IN STEM CELLS-BASED THERAPY FOR HIV ELIMINATION - Herdyan, Deta Intan; Ferni; Nugraha, Adi (Journal of Stem Cell Research and Tissue Engineering, 2025)
The persistent latent reservoir of HIV remains the greatest barrier to achieving a functional cure. Stem-cell–based therapy has emerged as a promising approach to eliminate or durably suppress HIV by reconstructing the immune system with HIV-resistant cells. This review summarizes recent progress (2021–2025) in stem-cell–based therapeutic strategies for HIV elimination, including hematopoietic stem cell transplantation (HSCT), gene-edited autologous stem cells, and stem-cell–derived engineered immune effectors. A narrative literature review was conducted using PubMed and Google Scholar databases for articles published between 2021 and 2025. Keywords included “HIV cure,” “stem cell therapy,” “hematopoietic stem cell transplantation,” “CCR5 gene editing,” “CAR-T cells,” and “HSPC-based HIV therapy.” Allogeneic HSCT using CCR5Δ32/Δ32 donors provided proof-of-concept for HIV elimination. Recent reports demonstrate additional remission cases using cord blood or haploidentical grafts. Advances in CRISPR/Cas9-mediated CCR5 disruption of autologous hematopoietic stem and progenitor cells (HSPCs) achieved high editing efficiency and successful engraftment. Stem-cell–derived CAR-T and CAR-NK cells showed potent antiviral effects in preclinical and early clinical studies. However, challenges remain in eradicating viral reservoirs, preventing viral escape, and ensuring long-term safety of gene editing. Stem-cell–based therapies represent a rapidly evolving frontier toward an HIV cure. Emerging technologies in gene editing and engineered cell therapy promise scalable, safer, and potentially curative approaches, though significant translational and ethical hurdles must be addressed before widespread clinical application.